1990
DOI: 10.1007/bf00187865
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the iodine molecule relevant to laser-induced fluorescence experiments in gas flows

Abstract: Laser-induced fluorescence of iodine seed molecules can be used for both flow visualization and accurate measurements of gasdynamic properties. This paper gives an introductory review of the use of iodine in experimental fluid mechanics, including basic formulas for saturated and non-saturated fluorescence (excited with narrowband or broadband lasers), line shape, line strength and quenching behavior. Techniques for the seeding of the molecules into the gas flow and the safe handling of the gas are discussed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…34 They argue that saturating the fluorescence, with the use of a continuous-wave excitation laser, allows the fluorescence signal to be independent of the quenching rate and laser intensity, which is desirable. With non-saturated fluorescence and a continuous-wave excitation laser, the PLIF signal, S f , is a function of the excitation laser power, I, fluorescence decay rate, A 21 , collisional quenching rate, Q, Boltzmann population fraction, F 1 , number density of the iodine species being irradiated, N I2 , and a correction for the optical collection geometry and molecular transition, C …”
Section: Coil Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 They argue that saturating the fluorescence, with the use of a continuous-wave excitation laser, allows the fluorescence signal to be independent of the quenching rate and laser intensity, which is desirable. With non-saturated fluorescence and a continuous-wave excitation laser, the PLIF signal, S f , is a function of the excitation laser power, I, fluorescence decay rate, A 21 , collisional quenching rate, Q, Boltzmann population fraction, F 1 , number density of the iodine species being irradiated, N I2 , and a correction for the optical collection geometry and molecular transition, C …”
Section: Coil Diagnosticsmentioning
confidence: 99%
“…Iodine PLIF can also been used to measure injectant mole fraction and iodine concentration in a flowfield. 35,34 With iodine present in COIL systems, using PLIF with iodine as the fluorescing species is an obvious choice for fluid imaging. There are several benefits to using iodine: it has a large absorption cross section, it fluoresces strongly in the visible, it has a high vapor pressure, and it has numerous transition lines across a large range of frequencies allowing the use of different laser wavelengths for excitation.…”
Section: Coil Diagnosticsmentioning
confidence: 99%
“…Flow visualization, 3 velocity, 4-7 pressure, 7, 8 temperature, 9 and density 4, 10 measurements have been made in flow fields using LIF of iodine with varying degrees of success. 11 Hiller and McDaniel 5 achieved an estimated accuracy of ± 10% when measuring velocity in subsonic gas flows. Hiller and Hansen 7 achieved errors of around 6% for both pressure and velocity measurements.…”
Section: Introductionmentioning
confidence: 98%
“…Iodine is a solid at room temperatures. Hiller&Hanson [3] have shown that the seeding concentration of iodine through sublimation from iodine crystals in a simple container is within 10% of the saturation value. However, the gas flow rate in their study was much smaller than for the Sandia flames.…”
Section: Implementation Of the Techniquementioning
confidence: 99%
“…However, iodine corrosion caused damage of the particle filter in a relatively short period of time and the deposition blocked the flow path. Another sublimation-based method using a fluidized-bed mixing chamber was proposed in [3], which, however, is difficult to achieve since iodine flakes tend to adhere to each other. To avoid these difficulties a different method involving liquid iodine and its evaporation is eventually employed in the present work (figure 1).…”
Section: Implementation Of the Techniquementioning
confidence: 99%